Intraoperative ketamine for reduction in postpartum depressive symptoms after cesarean delivery: A double‐blind, randomized clinical trial - Yao, Jiaxin; Song, Tingting; Zhang, Yue; Guo, Nan; Zhao, Ping (Brain and behavior, 2020)
Background Postpartum depression (PPD) is a common mental disease happens in perinatal period. Ketamine as an anesthesia and analgesia drug has been used for a long time. In recent years, ketamine is proved to have an antidepression effect with a single administration. We hypothesized that intraoperative ketamine can reduce postpartum depressive symptoms after cesarean delivery. Methods In a randomized, double‐blind, placebo‐controlled study trail, healthy women scheduled for cesarean delivery were randomly assigned to receive intravenous ketamine (0.25 mg/kg diluted to 5 ml with 0.9% saline) or placebo (5 ml of 0.9% saline) within 5 min following clamping of the neonatal umbilical cord. The primary outcome was the degree of postpartum depressive symptoms, which was evaluated by Edinburgh Postnatal Depression Scale (EPDS, a threshold of 9/10 was used) at 1 week, 2 weeks, and 1 month after delivery. The secondary outcome was the numerical rating scale (NRS) score of pain at 2 days postpartum. This trail is registered in the Chinese Clinical Trial Registry, number ChiCTR1900022464. Results Between 26 January 2019 and 15 July 2019, 502 subjects were screened and 330 were randomly allocated: 165 (50%) to the ketamine group and 165 (50%) to the placebo group. There were significant differences in the degree of postpartum depressive symptoms between subjects in the ketamine group and the placebo group at 1 week postpartum (13.1% vs. 22.6%, respectively; p = .029). However, no difference was found between subjects in the two groups at 2 weeks (11.8% vs. 16.8%, respectively; p = .209) and 1 month postpartum (10.5% vs. 14.2%, respectively; p = .319). The NRS score of wound pain (3.0 ± 0.9 vs. 4.0 ± 1.0, respectively; p < .001) and uterine contraction pain (3.0 ± 0.9 vs. 4.1 ± 0.9, respectively; p < .001) was lower in the ketamine group at 2 days postpartum compared with placebo group. The prevalence of headache, hallucination, and dizziness was higher in the ketamine group than the placebo group during the operation. Conclusions Operative intravenous ketamine (0.25 mg/kg) can reduce the postpartum depressive symptoms for 1 week. The long‐time effect is remained to be seen. Operative intravenous ketamine (0.25 mg/kg) can prevent postpartum depressive symptoms for 1 week. The long‐time effect is remained to be seen.